Study of physicians' preferences for optimizing the pharmacy assortment of glocose-lowering drugs - I. O. Vlasenko (The State Expert Center of the Ministry of Health of Ukraine, 2023)
For the stable operation of the pharmacy and the proper support of patients with diabetes, it is necessary to optimize the assortment of glucose-lowering drugs (GLD), taking into account the significant prevalence of this disease. The demand for prescription drugs is formed by doctors who choose therapy and prescribe drugs. The purpose of this study was to determine the factors that influence of choosing GLD for the treatment of type 2 diabetes and the preferences of doctors when choosing GLD for therapy. They used a remote questionnaire form using Google forms. 732 doctor questionnaires were processed. Statistical processing was carried out using structural, comparative and graphic analysis. A survey of doctors established the factors that influence the prescription of drugs for the treatment of type 2 diabetes: high effectiveness and inclusion of drugs in treatment standards, their safety, and their own positive experience in prescribing drugs. It was also found that when choosing a GLD type, almost half of doctors take into account the patient's purchasing power and the presence of a GLD in the reimbursement program. The survey showed that a third of doctors prefer domestic GLD, and half of the respondents do so sometimes. When choosing foreign medical medications, doctors prefer German, French, and Swiss-made medical drugs. A significant part of doctors do not have preferences when choosing trade name (TN), but the majority of doctors who have preferences prefer TN mainly of foreign production and prolonged forms. It was found that about 10% of the responding doctors do not prescribe combined GLD. The majority of respondent doctors have preferences for combinations: metformin/glimepiride, dapagliflozin propanediol/metformin and sitagliptin/metformin. Problems have been identified at the stage of pharmacological supervision of GLD. Despite the fact that doctors noted in their practice the side effects of drugs in patients, only a fourth (22.7%) of respondents recorded these effects in accordance with the current legislation and made reports. It is advisable to use the results of the questionnaire to improve the care of patients with diabetes and to meet their needs by optimizing the pharmacy assortment. It is advisable to increase the list of International Nonproprietary Name of GLDs for reimbursement, which will contribute to the availability of modern treatment regimens, because the price of medicines limits the quality of modern treatment regimens for type 2 diabetes.